Pengaruh motivasi kerja dan disiplin kerja terhadap kepuasan kerja serta dampaknya pada kinerja guru SMK - Syafaruddin Siregar; Hamonangan Siallagan; Gita Ginting (Jurnal Riset Manajemen dan Bisnis, 2022)
This study aims to determine the effect of work motivation and discipline on job satisfaction and its impact on teacher performance at a high school in Central Tapanuli Tengah. Data were collected by questionnaire involving 133 teachers. Structural Equation Modeling (SEM) with Partial Least Square (PLS) was used to test the hypothesis. The results of this study indicate that motivation and work discipline has a positive and significant effect on satisfaction and teacher performance. Job satisfaction has a positive and significant impact on teacher performance and mediates the relationship between motivation, work discipline, and teacher performance.